2000
DOI: 10.1080/10803548.2000.11076451
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Retention of Ultrafine Aerosol Particles in the Human Respiratory System. Normal and Pathological Cases

Abstract: The particle number concentration in ambient air is dominated by nanom eter sized particles. Recent epidemiological studies report an association between the presence of nanoparticles in inhaled air at the workplace and acute morbidity and even m ortality in the elderly. A theoretical model of deposition of 20 nm particles in the human alveolus was formulated. Gas flow structure and deposition rate were calculated for alveoli with different elastic properties of lung tissue. Data obtained in the paper show inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…During various processes, workers are exposed to various sizes of WC-Co particles including nanoparticles [32]. Recent evidence indicates that nanoparticles exhibit a higher deposition in all regions of the respiratory tract when compared to the fine particles, and that exposure to nanoparticles may induce cytotoxicity, pulmonary inflammation, and/or other adverse effects in the cells and lung [3]. However, the molecular mechanisms by which WC-Co exposure causes lung injury and carcinogenesis remain to be clarified.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During various processes, workers are exposed to various sizes of WC-Co particles including nanoparticles [32]. Recent evidence indicates that nanoparticles exhibit a higher deposition in all regions of the respiratory tract when compared to the fine particles, and that exposure to nanoparticles may induce cytotoxicity, pulmonary inflammation, and/or other adverse effects in the cells and lung [3]. However, the molecular mechanisms by which WC-Co exposure causes lung injury and carcinogenesis remain to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…There are increasing public concerns over the adverse health effects of exposure to nanoparticles and possible environmental impact of this emerging nanotechnology. Recent evidence has indicated that nanoparticles exhibit a higher deposition in all regions of the respiratory tract when compared to the fine particles, and that exposure to nanoparticles may induce cytotoxicity, pulmonary inflammation, and/or other adverse effects in the cells and the lung [2][3][4][5]. Once deposited in the airways, nanoparticles may migrate more rapidly to the interstitium and lymph nodes of the lung than the fine particles [6].…”
Section: Introductionmentioning
confidence: 95%
“…Токсикологические и эпидемиологические иссле дования базируются на предположениях о том, что причиной изменений в состоянии здоровья работаю щих могут быть ультрадисперсные частицы, посту пающие в организм ингаляционным путем [19,29]. Несмотря на то, что токсикологические механизмы таких эффектов недостаточно изучены, очевидно, что по сравнению с более крупными частицами, уль трамалые частицы обладают большей биологичес кой активностью и могут индуцировать интенсивные воспалительные реакции [16,30].…”
unclassified
“…На основании полу ченных данных было высказано предположение о су ществовании связи между отложением и задержкой наночастиц в легких с патологическими изменения ми легочной ткани (фиброз и ухудшение эластич ности). Рядом исследователей высказывается пред положение о том, что если воздействию ультрадис персных частиц предшествовала длительная экспо зиция частицами более крупного размера, обусло вившая возникновение патологических изменений легочной ткани, то ультрадисперсные частицы могут скапливаться в альвеолах, способствуя, таким обра зом, развитию эмфиземы легких [19,29,31 ].…”
unclassified
“…During various processes, workers are exposed to various particle sizes of WC-Co heavy metal including nanoparticles. Recent evidence indicates that nanoparticles exhibit a higher deposition in all regions of the respiratory tract when compared to the fine particles, and that exposure to nanoparticles may induce cytotoxicity, pulmonary inflammation, and/or other adverse effects in the cells and lung 36 . However, the molecular mechanisms by which WC-Co exposure causes lung injury and carcinogenesis remain to be clarified.…”
Section: Vegf and Angiogenesismentioning
confidence: 99%